2020
DOI: 10.1177/0267659120938928
|View full text |Cite
|
Sign up to set email alerts
|

Delayed graft function and perfusion parameters of kidneys from uncontrolled donors after circulatory death

Abstract: Better preservation and evaluation of kidneys from donors after circulatory death serve to increase the number of kidneys available for transplantation and hypothermic machine perfusion has been shown to decrease ischemia reperfusion injury and delayed graft function. Data on relation between hemodynamic parameters during hypothermic machine perfusion and delayed graft function in kidneys from donors after circulatory death are so far scarce and not univocal. We aimed at assessing whether hemodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Despite these measures, kidney recipients of uDCD donors typically present with acute tubular necrosis (ATN), observed as delayed graft function (DGF). [6][7][8][9][10][11][12][13][14] Acute rejection with differential diagnostic difficulties, vascular thrombosis, and prolonged hospitalization are routinely observed in these recipients. 8,12,15 Families of the deceased need time to provide donor consent after confirmation of a close relative's death.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these measures, kidney recipients of uDCD donors typically present with acute tubular necrosis (ATN), observed as delayed graft function (DGF). [6][7][8][9][10][11][12][13][14] Acute rejection with differential diagnostic difficulties, vascular thrombosis, and prolonged hospitalization are routinely observed in these recipients. 8,12,15 Families of the deceased need time to provide donor consent after confirmation of a close relative's death.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings showed that resistances at two hours and beyond predicted DGF, while initial resistance to machine perfusion predicted one-year graft survival post-transplantation [35]. On the other hand, some studies found no association between hemodynamic parameters during HMP and the development of DGF [27]. Thus, due to these inconclusive results, the perfusion parameters cannot be regarded as stand-alone criteria.…”
Section: Perfusion Controlmentioning
confidence: 99%
“…Static cold storage (SCS) and HMP are the main techniques of kidney graft preservation [26]. HMP has become a frequently and widely used procedure in kidney transplantation over the past few years [26][27][28]. Indeed, several reports have shown that the HMP reconditioning effect results in better postoperative outcomes with respect to reducing DGF and better long-term graft survival after transplantation [29][30][31].…”
Section: Perfusion Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, warm ischaemia arises prior to donation [13] and results in impaired delivery of oxygen and metabolic substrates [14,15]. This drives an anaerobic shift [14] and crucially ATP depletion [16], which results in widespread deterioration of tissue structure [17][18][19][20][21][22]. The warm ischemic injury incurred also stimulates damaging inflammatory responses [23].…”
Section: Warm Ischaemiamentioning
confidence: 99%